Making Decisions by Amateur Investors - Khalina, Natalia (Journal of Economic Sociology, 2013)
This article presents a review on “Pop Finance: Investment Clubs and the New Investor Populism” by B. Harrington. The book is devoted to investment clubs that were widespread on the American stock market in the 1990s. It was a way for attracting a mass of amateur investors on the market. In the beginning of there view the nature of investment club phenomenon is described; its meaning for the US economy in 1990 and reasons why many of ordinary Americans became a members of investment club are discussed. Next theme considered by Harringtonis a decision making process on the stock market in case of overwhelmingin formation. To guide their action amateur investors use mental maps reflecting their social identity. As a result, the decision to buy or to sell stocks is mediated not only by their financial performance, but also by the investor’s identity. All this ideas result in the debates about rationality of economic action. In addition, the significance of group composition is discussed. Why clubs composed of men and women together earned higher returns than all-male or all-female clubs? There is also the question how social ties within the group influence on investing and performance of the group. In conclusion, the author of the book review is trying to answer some other questions. How did the financial crisis of 2008 affect the performance of investment clubs? How could the ideas expressed in Harrington’s books be used for interpreting the situation on Russian stock market? Compared to USA stock market the share of personal investors in Russia is significantly smaller,nevertheless here we could find some examples which illustrate the influence of identity on the investment decisions.